SSRI-associated apathy in Alzheimer's disease: a case series - D. S. Petelin; A. N. Gamirova; O. N. Voskresenskaya; B. A. Volel (Неврология, нейропсихиатрия, психосоматика, 2022)
Apathy is one of the most common manifestations of neurodegenerative pathology, including Alzheimer's disease (AD). Despite such a significant role of apathy in the course of the disease, there are no unambiguous recommendations for the treatment and prevention of this symptom complex. Some classes of psychotropic drugs commonly prescribed for AD, such as antidepressants of the SSRI class, may themselves cause apathy. The authors present a series of clinical observations describing four cases of deterioration in the condition of patients with AD during SSRI therapy. The features of the clinical course of the disease are discussed, new strategies for drug therapy are proposed.